2021
DOI: 10.2147/idr.s330787
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genomic Analysis of NDM-5-Producing Enterobacteriaceae Recovered from an Urban River in China

Abstract: Three NDM-5-producing Enterobacteriaceae (Escherichia coli, Klebsiella pneumoniae, and Citrobacter braakii, one each) were isolated during a screening study for the presence of carbapenemase-producing Enterobacteriaceae (CPE) strains in urban rivers in China. The aim of the present study was to characterize these NDM-5-producing isolates by using whole-genome analysis. Methods: In vitro susceptibility testing was performed using the broth microdilution method. Conjugation assay was carried out to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…Focusing on hydric environments, this variant has been found in various environments such as urban waters [ 29 , 36 ]; rivers and lakes [ 8 , 37 ]; sediments and soil [ 38 ]; and seawater [ 8 ]. Various plasmid incompatibility groups carrying bla NDM-5 have been reported, with IncX-3 and IncF being among the most prevalent [ 8 , 27 , 34 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on hydric environments, this variant has been found in various environments such as urban waters [ 29 , 36 ]; rivers and lakes [ 8 , 37 ]; sediments and soil [ 38 ]; and seawater [ 8 ]. Various plasmid incompatibility groups carrying bla NDM-5 have been reported, with IncX-3 and IncF being among the most prevalent [ 8 , 27 , 34 , 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also higher than the prevalence of CREC (2.38%, 92/3895) in healthy people in healthcare centers located in 19 provinces across China [ 16 ]. The bla NDM gene was also detected from the specimens of various environments, vegetables (0.28%), companion animals (2.3%), and livestock and poultry (0.88%), the amounts of which were significantly lower than that in patients [ 33 , 34 , 35 ]. However, it has a similar prevalence in India (6.22%) [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, international circulation of NDM-5-producing E. coli was reported but only a few UPEC isolates harboring bla NDM-5 were identified [ 30 – 32 ]. To our knowledge, there are only 2 studies that reported the E. coli carrying bla NDM-5 in Taiwan [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%